The Clinical Function Comparison of Post Operative Nerve Grafting and Nerve Transfer in Patients with Brachial Plexus Injury - Agung Tristyanto1, Heri Suroto2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Brachial plexus injury is most commonly caused by motorcycle accidents and leads to a deficit of motor strength, pain and disability of the upper limb. The main purpose of reconstructive action of brachial plexus injury is to restore the function of the shoulder and elbow. Aim: This study aimed to compare the clinical function of post-operative nerve grafting with nerve transfer in patients with brachial plexus injury. Methods: This study enrolled a sample of patients who had surgery and evaluated the range of active movement of shoulder abduction and elbow flexion; motor strength using the scale of the British Medical Research Council (BMRC); neuropathic pain using Visual Analog Scale (VAS); and upper extremity disability using the Quick Disability of the Arm, Shoulder, and Hand (Quick DASH) questionnaire. Results: 30 patients were divided into groups of nerve grafting and nerve transfer with each group consisting of 15 patients. 13 patients (87%) of each group had motor strength of functional shoulder abduction (>M3) (p = 0.874). 13 patients (87%) had better functional elbow flexion motor strength (>M3) in the nerve transfer group than 11 patients (73%) of the nerve grafting group (p = 0.036). Conclusion: The postoperative nerve transfered clinical function showed a better elbow flexion function with a lower severity of upper limb disability.